Performance Assessment of Phase Change Material in Thermal Energy Storage Systems under Different Heat Transfer Fluid Pipe Configurations - Kıyak, Burak (My University, 2026)
This study presents a three-dimensional numerical investigation on the melting performance and energy storage characteristics of a shell-and-tube latent heat thermal energy storage (LHTES) unit filled with RT35HC phase change material (PCM). Five different heat transfer fluid (HTF) tube configurations—Straight, 1P-1T, 1P-2T, 2P-1T, and 2P-2T—were analysed under both horizontal and vertical orientations. In single-tube designs, the HTF surface area was equalized to evaluate the effect of geometry on the melting process independently. In multi-tube/multi-turn helical designs, the combined influence of increased surface area and reduced PCM volume was considered. Performance evaluation was carried out in terms of liquid fraction, stored energy, average heat flux, and average Nusselt number. The analyses revealed that, in vertical orientation, the 2P-2T configuration stored 122.6% more energy than the Straight configuration, with a significantly shorter melting duration. These findings emphasize the critical role of tube geometry and system orientation in influencing melting dynamics and energy storage efficiency, providing valuable guidance for LHTES system design optimization.
Keywords: CFD; Phase change material; Shell-and-tube heat exchanger; Latent heat storage; Helical pipe